Effect of Health Education on Mothers’ Knowledge in the Prevention of Acute Respiratory Infection in Toddlers in Waimital Village, Maluku - Ira Sandi Tunny; Idham Soamole; Suhendra Agung Wibowo; Ira Purnamasari; Wiwi Rumaolat (Jurnal Ners, 2020)
ABSTRACTIntroduction: Acute Respiratory Infection (ARI) is a disease caused by infectious agents that are usually toddlers, so it is expected that the family, especially the mother, plays a role in terms of having good knowledge about the prevention of ARI transmission.  Health education through visual aid leaflets is very effective to increase knowledge and understanding in preventing ARI disease.  The aim of this study was to determine the effect of health education on the level of maternal knowledge in the prevention of ARI in children under.Methods: The research design used was a pre-experiment with one group and a pretest-posttest design approach.  Intervention was carried out by way of house visits on a sample of 129 people. The research instrument used was questionnaire data analysis using the Wilcoxon test at a significance of (α <0.05).Results: Before doing health education, good knowledge was seen in 2 respondents or 1.6% and after the action of health education using leaflets, good knowledge was seen in 33 respondents or 25.6%. Statistical analysis of respondents' knowledge after treatment obtained an average value for knowledge of 68.84; the lowest value was 30 and the highest was 100, significant with a p-value = 0.000 (α <0.05).Conclusion: Health education using leaflets can increase mothers' knowledge so that it encourages self-efficacy and self-management and increases awareness in the prevention of disease.  There is an influence of health education on the level of maternal knowledge in the prevention of ARI among children under five.